Oviranosti in potrebe po rehabilitaciji ambulantnih bolnikov s shizofrenijo - Groznik, Matjaž (Medicinski razgledi, 1999)
The aim of this study was to identify the symptoms, disabilities and needs of schizophrenic outpatients. Fifty schizophrenic outpatients (5 % sample, 31 males and 19 females; mean age 43 years) receiving maintenance depot neuroleptic therapy were enrolled in this cross-sectional study. The patients were interviewed using standardized scales. The female patients were found to have been employed for a longer period than males (p < 0.01 ). Most patients had disability pension and lived with their parents, while females had more frequent contacts with their partners than wilh their parents. The quality of life was positively correlated with female sex, broader social network and longer period of employment. The most frequently reported needs referred to the management of psychotic symptoms and physical health, company, housekeeping skills and preparation of meals. The patients' needs were not satisfied in the following areas: company, information about the condition andtreatment, accommodation, physical health, daytime activities, psychological distress, money, benefits, sexual expression. Local services proved inadequate, particularly as concerns the management of psychotic symptoms. The patients were more satisfied with the role of of their relativesand friends in satisfying their social needs. It was found that the patients were poorly informed about the available services; therefore more emphasis should be placed on this aspect of patient education. Further research should be directed to the evaluation of the complementarity of different services, as well as to the formulation of strategies for a more effective service provision.
Keywords: Schizophrenia; shizofrenija; vocational rehabilitation; rehabilitacija; Rehabilitation; bolniki; Disability evaluation; oviranost; Quality of life; kvaliteta življenja; Outpatients; Questionnaires; Socioeconomic factors; Sex factors